Patterns of pharmacologic treatment in US patients with acromegaly. (3rd May 2016) - Broder, Michael S.; Chang, Eunice; Ludlam, William H.; Neary, Maureen P.; Carmichael, John D.
Abstract: Objective: To establish a baseline pattern of care across academic and community settings, it is important to examine the contemporary treatment of acromegaly. We characterized medical treatment patterns for acromegaly in the US to develop a basis for tracking concordance with guidelines. Research design and methods: Acromegaly patients were identified in two commercial claims databases for this retrospective analysis. Study subjects had ≥2 medical claims with acromegaly (ICD-9-CM code 253.0) and ≥1 claim for pharmacotherapy (bromocriptine, cabergoline, octreotide SA, octreotide LAR, lanreotide, or pegvisomant) in the study timeframe (1 January 2002–31 December 2013). Patients were considered newly treated if they were continuously enrolled for ≥6 months before first observed treatment and had no claim for pharmacologic treatment during that time. Outcomes included various pharmacotherapies, including combination treatments, and differences between lines of therapy. Results: A total of 3150 patients had ≥1 pharmacotherapy (mean age: 46.5 years; 50.1% were female); 1471 were newly treated. Somatostatin receptor ligands (SRLs) were the most common drug class used first line (57.2%); cabergoline (27.8%) was the most common treatment, followed by octreotide LAR (22.3%) and lanreotide (19.7%). SRLs were also the most commonly used second-line (42.8%) and third-line pharmacotherapies (43.9%), with combination therapy (23.2%) and octreotide LAR (19.8%) as the most commonly used treatments, respectively. Conclusions: This study, representing the largest claims-based analysis of acromegaly to date, used two databases across a 12 year period to examine complex treatment patterns in a difficult-to-study disease. Although wide variation in acromegaly treatment patterns exists in US clinical practice, in first-line, second-line, and third-line therapy, SRL was the most commonly used drug class. Drug combinations also varied considerably across lines of therapy. The switching between different monotherapies and varied use of drugs in combination may suggest an unmet need for alternative treatment options. Our claims-based technique of examining treatment patterns may be used for other rare diseases, although high censoring rates may be a challenge.